"Análisis y simulación de protocolos de enrutamiento adecuados en diferentes escenarios para redes AdHoc, mediante la herramienta Ns-3". - Rodríguez Pineda, Gabriela Maribel (2016)
For the accomplishment of the present certification Project the following steps were followed: first identification of the problem, objectives approach, state of the art, along with the list of tasks that define the methodology, which allowed to offer a solution to the problems through phases. A deep analysis of the information collected related to the Ad, hoc networks took place, using the deductive and inductive methods, where it was possible to identify the main drawbacks, among them there is the so- called hidden nodes, which is mainly associated with the wrong type of routing, and therefore the study of protocol usage was initiated according to these networks, using the network simulation tools spanish words “ Simulación de Redes” Ns-3 (open source), one of the best alternatives for Ad-Hoc networks and to manage them in a simulated environment. We proceeded with the execution of the phases which is totally planted by the methodology, starting from a deep analysis of the Ad-Hoc networks and it’s protocols, continuing with the specification of two stages and four protocols, which they were performed on the simulation stage which also involves a coding programming language (c++), which resulted a set of metrics that were used to evaluate the performance of the networks according to the stage and the protocols that were used. After this we proceeded to perform a comparison of the metrics and the four protocols used key words: (AODV, DSR, OLSR, DSDV), on two stages and in order to make a proposal based on this study, aimed to the stabilization of Ad-Hoc networks, based on improving routing in this case, using the appropriate protocols.